Tobacco and alcohol: complements or substitutes? A statistical Guinea Pig approach - Till Requate; Silja Göhlmann; Harald Tauchmann; Christoph M. Schmidt (Kiel University, Department of Economics, 2006)
The question of whether two drugs - namely alcohol and tobacco - are used as complements or substitutes is of crucial interest if side-effects of anti-drug policies are considered. Numerous papers have empirically addressed this issue by estimating demand systems for alcohol and tobacco and subsequently calculating cross-price effects. However, this traditional approach often is seriously hampered by insufficient price-variation observed in survey data. We, therefore, suggest an alternative instrumental variables approach that statistically mimics an experimental study and does not rely on prices as explanatory variables. This approach is applied to German survey data. Our estimation results suggest that a reduction in tobacco consumption results in a reduction in alcohol consumption, too. It is shown theoretically that this implies that alcohol and tobacco are complements. Hence, we conclude that successful antismoking policies will not result in the unintended side-effect of an increased (ab)use of alcohol.
Keywords: C31; I12; D12; 330; interdependence in consumption; tobacco and alcohol; instrumental variables approach; Drogenkonsum; Rauchen; Alkoholkonsum; Konsuminterdependenz; Komplementärgut; Instrumentalvariablen-Schätzmethode; Schätzung; Deutschland